Pendampingan Pengembangan E-Modul berbasis Microlearning bagi Guru SMA Negeri 9 Makassar - Saparuddin; Andi Baso Kaswar; Dian Dwi Putri Ulan Sari Patongai; Muhiddin Palennari; St. Fatmah Hiola; Sahribulan (Ininnawa : Jurnal Pengabdian Masyarakat, 2023)
The progress of science and technology in the world of education has made academics adapt to new conditions due to social change. The teacher is the front guard in the class who can provide great opportunities to make the learning atmosphere more interesting and fun. Teachers with innovative skills will become agents of reform who can change the generation of the nation's children for the better through an innovative and interesting learning system. To achieve the quality of learning, teachers must have competence, one of which is pedagogical competence in planning the learning process. The learning planning referred to in this activity is the development of e-module-based learning media. The purpose of this training and mentoring is to increase knowledge and skills in creating microlearning-based e-modules for teachers of SMA Negeri 9 Makassar. The Community Partnership Program is carried out in 3 main stages, namely the preparation, implementation and evaluation stages. The results of this activity are increasing the skills and knowledge of service participants in making other variations of learning media to be used as learning resources, assisting in using variations of learning methods other than conventional, can also familiarize trainees with technology in preparing learning resources.